ON THE SYMMETRIC VECTOR QUASI-EQUILIBRIUM PROBLEM VIA NONLINEAR SCALARIZATION METHOD - Farajzadeh, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
The aim of this paper, among other things, is, using a nonlinear scalarization function and its properties, to study an existence theorem for a solution of SVQEP in the setting of real topological vector space. One can consider this note as a new version of the reference [5] by replacing a nonlinear scalarization function by a linear functional.